Sheep rumen digestion and transmission of weedy Malva parviflora seeds - Michael, Pippa; Steadman, K.; Plummer, J.; Vercoe, P. (CSIRO Publishing, 2006)
The effect of sheep digestion and mastication on Malva parviflora seed transmission, viability and germination was investigated. Mature M. parviflora seeds were subjected to two seed treatments; ‘scarified’, where the hard seed coat was manually nicked allowing imbibition, and ‘unscarified’, where the hard seed coat was untouched. Seeds were placed directly into the rumen of fistulated sheep and removed at 0, 12, 24, 36 and 48 h of rumen digestion. After 12 hours of in sacco exposure to digestion in the rumen, the germination of seeds that were initially scarified dropped from 99.2% to 1.4% and longer exposure periods produced no germinable seeds. In contrast, seeds that were unscarified when placed in the rumen produced over 92% germination regardless of in sacco digestion time, but manual scarification after retrieval was essential to elicit germination. In a second experiment unscarified seeds (29,000) were fed in a single meal to fistulated sheep and faeces were collected at regular intervals between 6 and 120 h after feeding. Faecal sub-samples were taken to determine number of seeds excreted, seed germination on agar and seed germination from faeces. Major seed excretion in the faeces commenced after 12 h and continued until 144 h, with peaks between 36 and 72 h after consumption. Although mastication and gut passage killed the majority of unscarified seeds fed, approximately 20% were recovered intact and over 90% of these recovered seeds were viable and could thus potentially form an extensive seed bank. A few excreted seeds (1%) were able to germinate directly from faeces, which increased to a maximum of 10% after subsequent dry summer storage (3 months). Through information gained in this study, there is a potential to utilise livestock in an integrated weed management program for the control of M. parviflora provided additional measures of weed control are in place such as holding periods (>7 days) for movement of livestock from weed infested areas.